(untitled) (International Journal of Engineering and Computer Science, 2018)
Users can utilize powerful computing resources in cloud computing, which brings users great convenience. However, cloud computing is also facing many challenges for data security as the users outsource their sensitive data to clouds, which are generally beyond the same trusted domain as data owners. To address this problem, access control, which grants access permissions to an authorized user, is considered as one of critical security mechanisms for data protection in cloud computing environment. However, due to the unpredictability of user identities and access behavior, access control in cloud computing has become a key security problem. In this project, we propose a self-adaptive access control model based on secure cloud computing environment. The secure cloud computing environment includes analyzer Engine, Detection Engine, Rollback Engine, execute parts and knowledge base, and the knowledge base is used to make decisions on access requests. We also propose our own algorithm to create the Secure Engine. The self-adaptive access control model based on Secure Cloud Computing Environment we proposed can be applied to cloud computing environment.